Haemolysis related to mitral valve replacement with the Beall valve prosthesis. Issue 4 (July 1973) - Henderson, B. J.; Mitha, A. S.; le Roux, B. T.; Gotsman, M. S.
Abstract : Henderson, B. J., Mitha, A. S., le Roux, B. T., and Gotsman, M. S. (1973). Thorax, 28, 488-491. Haemolysis related to mitral valve replacement with the Beall valve prothesis. Experience of valve replacement with the Beall compressed Teflon disc valve in 59 patients confirms that the incidence of clinically significant late red cell destruction is high. An apparently previously unrecorded high incidence of early haemolysis, so severe in one patient as to be directly the cause of death, is reported. In 29 patients there was massive haemolysis in early convalescence, not recognized in urine from some hours after the end of bypass and never encountered with other designs of prosthetic valve or homograft valve.